The verb in Transformational obstetric Linguistics - Saadoon, Haider Kamil; Jebur, Hayder Mohammed (Al-Adab Journal, 2021)
The Arab viewpoint differed with Chomsky in terms of the actual corner arrangement pattern in the sentence, although some Arab generators say so. Because the rules of the English language are not reflected in Arabic, But the deletion of verbs represents an omission of a basic corner of the sentence, and it must be done according to certain controls. This research studies the verb as a vital element in the generative approach. Because he took center stage in the profound structure that this curriculum places at the fore.